DEVELOPMENT OF THE EDUCATIONAL GAME ‘FRACTIFY’ BASED ON CONSTRUCT 3 SOFTWARE AS A LEARNING MEDIA FOR FRACTION MATERIAL IN FOURTH GRADE ELEMENTARY SCHOOL - Anggoro, Rizky Tri; Arafah, Andi Asrafiani; Sukriadi, Sukriadi; Rahmi, Rosita Putri; Iksam, Iksam; Wahyuningsih, Tri (JURNAL NALAR PENDIDIKAN, 2024)
This study aims to develop Fractify, an educational game designed as an engaging and enjoyable learning tool for fraction concepts. The research utilizes a Research and Development (R&D) method with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The study was conducted with fourth-grade students and teachers from SD Negeri 021 Sungai Kunjang, with data collected through questionnaires, interviews, and observations. The validation results show that Fractify is highly valid, with scores of 92% from content experts, 90% from language experts, and 90% from media experts. Teacher and student responses were also very positive, with a practicality score of 88% from teachers, 94% from students in a small-scale trial, and 92% in a large-scale trial. Additionally, N-Gain data indicated an improvement in student understanding from pre-test to post-test, with an average N-Gain score of 0.6 (medium category), proving that Fractify is effective in enhancing mathematics learning. In conclusion, Fractify is effective and suitable for use as a learning tool for teaching fractions in elementary schools.